Effectiveness of Guided Imagery Therapy in Reducing Pain Among Adult Post-Appendectomy Patients: A Quasi-Experimental Study - Rilla, Eldessa Vava; Fauzan, Suhaimi (Chakra Brahmanda Lentera Institute, 2026)
Background: Pain is a common complaint among postoperative patients, including those undergoing appendectomy. Guided imagery therapy is a non-pharmacological intervention that can help reduce pain by diverting patients’ attention from discomfort with minimal side effects. However, evidence regarding its effectiveness in adult post-appendectomy patients remains limited. This study aimed to determine the effect of guided imagery therapy on reducing pain intensity in adult post-appendectomy patients. Methods: This study used a quasi-experimental design with a pretest-posttest control group, conducted in accordance with the TREND reporting guidelines. This study received ethical approval from the Research Ethics Committee of the Karsa Husada Garut College of Health Sciences. The sample consisted of 50 patients, equally divided into intervention and control groups (25 per group), recruited according to the inclusion and exclusion criteria. The independent variable was guided imagery therapy administered twice a day for 15–20 minutes over three consecutive days by the researcher, while the dependent variable was pain intensity measured using the Numeric Rating Scale (NRS). The control group received routine care. Data were analyzed using the Mann-Whitney test for differences between groups, with a significance level of 0.05. All statistical analyses were performed using IBM SPSS Statistics version 29. Results: The intervention group showed a significant reduction in pain intensity (p<0.05). The intervention group demonstrated a marked reduction in mean pain scores from 4.88 at pretest to 1.68 at posttest, representing a very large within-group effect. In contrast, the control group showed only a minimal change from 4.84 to 4.44. Between-group comparison indicated a significantly greater reduction in pain in the intervention group than in the control group. All main statistical results are presented with 95% confidence intervals to provide an estimate of precision and uncertainty around the observed effects. Conclusion: Guided imagery therapy has been shown to significantly reduce pain intensity in adult patients after appendectomy compared to the control group. It is recommended that nurses teach and provide guided imagery therapy regularly to reduce pain intensity in adult post-appendectomy patients